Análise da relação entre o mercado imobiliário de armazéns e a acessibilidade aos lugares centrais na Região Metropolitana de Belo Horizonte - Marcela Cristina Costa Branco (2023)
In the context of the logistic real estate market, transformations driven by e-commerce and urban configuration play a crucial role in the distribution of goods, especially concerning the last mile and home deliveries. Against this backdrop, this research primarily aims to identify central places (a proxy of consumer market concentration) and to investigate the relationship between warehouse rental pricing and the accessibility of these facilities to the central places. The study is set in the warehouse real estate market in the Metropolitan Region of Belo Horizonte (RMBH) and follows a structure consisting of three main axes. These axes include the analysis of the warehouse real estate market, the identification of central places within RMBH, and the assessment of the accessibility of warehouses to these central places. For the identification of central places, data from Points of Interest (POIs) from OpenStreetMap (OSM) in the RMBH hexagons were used. The gravitational model was employed for the accessibility evaluation. Lastly, the research examined the correlations between warehouse rental prices and the accessibility of these facilities concerning the central places. The results of this research revealed that when applying the Spearman correlation test, a positive and weak correlation was observed between the accessibility of warehouses to the central places and the rental prices per square meter per month of these facilities in areas of very strong centrality, regardless of the mode of transportation used, whether by car, bicycle, or on foot. However, when considering the central places without distinguishing centrality subcategories, the Spearman correlation turned out positive and moderate for areas of very strong centrality using the same transportation modes mentioned. Thus, it is not possible to affirm that the level of warehouse accessibility to central places is directly related to the rental prices of these facilities. The Spearman correlation analysis revealed another interesting bias: the accessibility of warehouses, considering modes of transport (car, bicycle, and on foot) for localities of intermediate centrality, showed a negative correlation with the rental prices of these facilities per square meter per month. This suggests that warehouses with higher accessibility to locations of intermediate centrality tend to have lower rental prices. This pattern also applies to locations of weak centrality when considering transportation by bicycle. Therefore, it is relevant to consider future studies for a more in-depth analysis of these phenomena. Through the KruskalWallis test, significant differences in the accessibility of warehouses to centrality subcategories were observed. However, when applying the Dunn’s multiple comparisons test, between centrality subgroups, warehouse accessibility to intermediate and strong centrality showed equal significance when it comes to walking transportation mode. This suggests the need for further investigations to understand the factors underlying this phenomenon. On the other hand, through the Wilcoxon test, it’s not possible to assert that warehouse rental prices are higher in the central places of the RMBH.